Optimizing Gastrointestinal Integrity in Poultry: The Role of Nutrients and Feed Additives - Adedokun, Sunday A.; Olojede, Opeyemi C. (Frontiers in Veterinary Science, 2019)
Immunomodulation of the immune system by stimulating or suppressing one or both arms of the immune system is an emerging concept driven by the understanding of the host defense system. Particularly, the gastrointestinal tract (GIT), not only function as a site for digestion and absorption of nutrients but also acts as a metabolic and immunological organ that serves as a barrier against abnormal presentation of luminal constituents, caused by dysfunctional intestinal epithelial barrier, to the mucosal immune system. Invasion by pathogens in the case of disease or stress or a massive influx of commensal bacteria overcomes the defensive mechanisms, resulting in the full activation of local dendritic cells and the expression of co-stimulatory molecules and pro-inflammatory cytokines. A growing body of literature demonstrates the immune benefits of increasing the intake of specific nutrients. This strategy involves formulating diets that encompass the bioavailability and utilization of nutrients from various food sources and understanding the dynamics of the macro and micronutrients to support all physiological functions as well as maintaining the function of the immune cells. The nature and type of feed ingredients may also play some roles on the integrity of the GIT of birds. Because dietary intake or nutritional status as well as nutrient requirements may be altered as a result of disease or stress, this may eventually alter the gut microflora and intestinal mucosal integrity, resulting in a compromised barrier of the intestinal epithelium. The weakening of the intestinal integrity could result in an increase in bacterial adherence to the mucosa, bacterial translocation, susceptibility to opportunistic bacterial infection, and mis-appropriation of nutrients. In this chapter, we will discuss the role of dietary energy and nutrients as substrates that have the potential to influence GIT’s health and integrity and their roles, directly or indirectly, in modulating birds ability to be resilient or resist infection. Additionally, the role of exogenous enzymes and feed additives in enhancing prececal energy and nutrient digestion and absorption are discussed.